2018
DOI: 10.3325/cmj.2018.59.46
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the interleukin-1β-induced inflammatory response of human Chang liver cells by acute and subacute exposure to alcohol: an in vitro study

Abstract: AimTo evaluate protective immunosuppressive dose and time-dependent effects of ethanol in an in vitro model of acute inflammation in human Chang liver cells.MethodThe study was performed in 2016 and 2017 in the research laboratory of the Department of Trauma, Hand and Reconstructive Surgery, the University Hospital of the Goethe-University Frankfurt. Chang liver cells were stimulated with either interleukin (IL)-1β or IL-6 and subsequently treated with low-dose ethanol (85 mmol/L) or high-dose ethanol (170 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Interestingly, the ROS-reducing effects of alcohol were observed also after 24 h in monocytes, demonstrating prolonged suppressive influence of an acute intoxication with alcohol. The alterations regarding the ROS production during the observational timeline may be in line with findings reported by others demonstrating that the ROS production in human Chang liver cells depends on concentrations of alcohol to which the cells were exposed [28].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the ROS-reducing effects of alcohol were observed also after 24 h in monocytes, demonstrating prolonged suppressive influence of an acute intoxication with alcohol. The alterations regarding the ROS production during the observational timeline may be in line with findings reported by others demonstrating that the ROS production in human Chang liver cells depends on concentrations of alcohol to which the cells were exposed [28].…”
Section: Discussionsupporting
confidence: 90%
“…Inflammasome components are present in multiple cell types, including HepG2 cells (Figure 3) [45,46]. The rationale for using HepG2, which is most commonly used in drug metabolism and hepatotoxicity studies [47], was determined by the fact that our and others' previous studies have already revealed the significant anti-inflammatory effects of acute alcohol administration upon the induction of inflammatory processes in various cell entities, including lung epithelial cells [28][29][30]48], human endothelial cells [49], macrophages and others [38,50]. Though the main mechanisms underlying the anti-inflammatory potential of acute ethanol intoxication under inflammatory conditions were linked to NF-κB [17], the impact of acute ethanol application on inflammatory processes specifically in terms of inflammasome functionality is mechanistically poorly investigated in hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme Linked Immunosorbent Assay (ELISA) technique was used to measure, serum levels of Interlukine-6 (IL-6 ELISA Kit Dublin, Ireland), in diabetic patients with & without complication diabetes type2 and control group (18,19) Fasting Blood Glucose (FBG): Glucose was determined after enzymatic oxidation in the presence of glucose oxidase . The hydrogen peroxide formed reacts under catalysis of peroxidase, with phenol and 4-aminophenazone to form a red-violet quinoneimine dye as indicator (20) .…”
Section: (Il-6)mentioning
confidence: 99%